Journey decision making: the influence on drivers of dynamic information presented on variable message signs - Sharples, Sarah; Shalloe, Sally; Burnett, Gary; Crundall, David (Springer, 2016)
In many highways environments electronic media such as variable message signs are increasingly being used to provide drivers with up-to-date dynamic information in order to influence driving decision making during journeys. These decisions may be associated with strategic choices, such as route selection, or tactical decisions, such as driving at a certain speed, or altering driving style. This paper presents a study that used two methods—a scenario approach and a medium-fidelity driving simulator. Data from both methods are presented here and include decision making and driving performance data. These data provide an insight into the role of information and other contextual influences in decision making in the driving context specifically, but also has useful implications for the way in which information should be designed in other decision making contexts, such as travel using public transport, or supporting real-time complex control operations. The use of multiple data collection approaches also enabled data comparisons to be made, thus improving overall confidence in conclusions. The paper highlights the role of familiarity with information wording and context, level of detail, interpreted meaning, previous experience and contextual cues on trust in information and consequently behaviour in response to the information presented.